Resposta à sigatoka amarela e desenvolvimento vegetativo de genótipos de bananeira nos Tabuleiros Costeiros : 1º ciclo - Quirino, Zilna Brito de Rezende (2010)
Jatropha curcas L. (Euphorbiaceae) has attracted considerable interest in recent years because of its high potential to provide oil for the production of biofuel. This interest has resulted in increased investments in the cultivation of J. curcas in many areas all over the world. However, J.curcas remains an un-domesticated crop and there is a lack of scientific evidence for its productive potential and agronomic properties. This situation could lead to unsustainable practices with economic, social and environmental risks. To reduce these risks and to improve the performance of the J.curcas in different agroclimatic conditions, it is very important to invest in the domestication, selection and genetic breeding of J.curcas. At this point, it is necessary to know the degree of genetic diversity of the species in natural, isolated cultivated, commercial and experimental populations. Due to the importance in this area, this work had as objective to genetically characterize genotypes of J. curcas cultivated in experimental areas in two cities of Sergipe, State of Brazil (Umbaúba and Carira) by means of molecular markers RAPD. The methodology of DNA extraction from leaves of 40 genotypes, collected in the cities of Umbaúba and Carira, was carring out according to method CTAB 2% and to DNA amplification were used 31 primers of arbitrary sequence. DNA markers were scored for the presence (1) and absence (0) of homologous amplified, which were used in the construction of the binary matrix in order to calculate the percentage of polymorphism of each primer used. This data was also used to estimate the genetic similarity among the pairs of genotypes, using Jaccard coefficient, and group them out for the UPGMA and PCoA methods. Afterwards, the similarity error associated with the minimum value of similarity was calculated. Fragments (101) were generated from 31 primers, 30 of which were polymorphics. A similarity average of 0,54 (±0,09) among the genotypes was found and the amplitude similarities varied from 0,18 (±0,07) to 1,00 (±0,00). The average genetic similarity was equal to 0,67, and from this value it was possible to observe the formation of nine clusters. Two of them were unit clusters and formed by the most divergent genotypes, three and five. In conclusion, it was not possible verify low genetic variability in physic nut using RAPD markers at these experimental areas.